Evaluation of Panchelonioidea (Testudines: Cryptodira) evolution based on phylogenetic morphometrics - Goulart, Isabella Vasconcellos (2021)
This study presents a cladistic hypothesis based on morphogeometric data, known as Phylogenetic Morphometrics. The analysis was conducted investigating 11 landmark con- figurations (carapace, coracoid, humerus, iltum, ischium, jJaw, plastron, pubis and skulldorsal, ventral and lateral) of 31 species of sea turtles. These configurations represent a set of anatomical landmarks that retamn the general shape of a structure and allow to map morphological differences between taxa with less subjectivity than with discrete characters. Although some inconsistencies persist, such as internal relationships and the phylogenetic definition of Cheloniidae, the results elucidate some aspects about the evo- lution of Panchelonioidea. Ctenochelys procax and Toxochelys latiremis were recovered as, respectively, the first two divergence nodes of Panchelonioidea. The Cretaceous stem-Cheloniidae, Euclastes wielandi and Allopleuron hofmanni, were nested separately from the other species of Cheloniidae, showing more affinity with the Upper Cretaceous clades than with Cenozoilc sea turtles, so, E. wielandi was reallocated to Ctenochelyidae. The composition of Dermochelyoidea sensu Evers & Benson, 2019 1s supported by our data and Allopleuron presumably has a greater affinity with this clade than with Panche- lonidae. The Paleogene Cheloniidae were placed in two strongly supported groups, with Eochelone as the first diverging taxon. Despite being positioned outside Panchelonioidea, there 1s no concrete evidence supporting Mesodermochelys undulatus as stem-Cryptodira. Ocepechelon bouyai was recovered mn Protostegidae and the results confirm that the former members of “Osteopygidae” have different origins (independent lineages). The fact that Protostegidae 1s recovered within the Chelonioidea crown-group 1s controversial and implies an extensive ghost lineage for most Cheloniidae, so 1t 1s possible that this positioning 1s the result of evolutionary convergence, probably comprising pelagic specializations that masked part of the phylogenetic signal in the analysed data. Keywords: Panchelonioidea. Sea turtle. Fossil turtle. Palacontology. Parsimony. Pro- crustes. Phylogenetic Morphometrics. Geometric Morphometrics. TNT.